2020
DOI: 10.1039/d0qi00685h
|View full text |Cite
|
Sign up to set email alerts
|

Axial functionalisation of photoactive diazido platinum(iv) anticancer complexes

Abstract: Mono-functionalised diazido Pt(iv) anticancer complexes release Pt(ii) species and radicals upon irradiation. Their di-functionalised analogues with an additional dichloroacetate ligand show improved photocytotoxicity and photo-generated ROS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…Coumarin itself can act as a light-harvesting antenna and also possesses intrinsic anticancer activity. Interestingly, Pt2 generates blue fluorescence upon irradiation (λ em = 440 nm), attributable to the formation of fluorescent coumarin species upon photoactivation with 465 nm light in aqueous solution . UV–vis spectroscopic studies of the photodecomposition of Pt2 have suggested rapid loss of the azide ligands (within 15 min) upon irradiation with blue light (λ = 420 nm) but high stability under dark conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coumarin itself can act as a light-harvesting antenna and also possesses intrinsic anticancer activity. Interestingly, Pt2 generates blue fluorescence upon irradiation (λ em = 440 nm), attributable to the formation of fluorescent coumarin species upon photoactivation with 465 nm light in aqueous solution . UV–vis spectroscopic studies of the photodecomposition of Pt2 have suggested rapid loss of the azide ligands (within 15 min) upon irradiation with blue light (λ = 420 nm) but high stability under dark conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Pt2 generates blue fluorescence upon irradiation (λ em = 440 nm), attributable to the formation of fluorescent coumarin species upon photoactivation with 465 nm light in aqueous solution . UV–vis spectroscopic studies of the photodecomposition of Pt2 have suggested rapid loss of the azide ligands (within 15 min) upon irradiation with blue light (λ = 420 nm) but high stability under dark conditions. Likewise, electron paramagnetic resonance (EPR) studies revealed the formation of • OH and • N 3 radicals upon photoactivation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further investigate the effects of axial functionalization, three mono-functionalized diazido Pt(IV) prodrugs attaching to anticancer agent coumarin-3 carboxylate (cou), PDK inhibitor 4-phenylbutyrate (PhB), or DCA (complexes 83 – 85 , Table 8 ) and three biaxially functionalized prodrugs with further modification with a DCA ligand (complexes 86 – 88 , Table 8 ) were developed ( Shi et al, 2020a ). Notably, mono-functionalized complexes ( 83 – 85 ) with one hydroxide ligand showed higher aqueous solubility and more negative reduction potential, while significantly higher cellular Pt accumulation (ca.…”
Section: Axial Ligandmentioning
confidence: 99%
“…Since this modification also has the potential to lead to more facile spontaneous reduction in the dark, evaluation of stability of the complex in the absence of irradiation is important. Modification of the axial ligands of photoactivatable Pt( iv ) diazido complexes to incorporate biotin, 14 guanidinoneomycin, 15 coumarins 16 and naphthalimides, 17 as well as an RGD peptide to target integrin 18 have been reported. However, the synthesis and extensive characterisation of 1 itself has not been reported previously, and we report it here for the first time along with two other complexes.…”
Section: Introductionmentioning
confidence: 99%